PENGARUH DUKUNGAN ORGANISASI DAN KOMITMEN AFEKTIF TERHADAP OCB GURU SMP NEGERI DI KECAMATAN CAKUNG JAKARTA TIMUR - Susi Nurhayati (Universitas Negeri Jakarta, 2014)
The purpose of this research is to comprehensively understand about the effect of perceived organizational support and affective commitment to public junior high school teacher’s organizational citizenship behavior (OCB) in District of Cakung, East Jakarta. The research methodology was survey which was selected by simple random sampling technique. Analysis and interpretation of the data indicate that (1) perceived organizational support has a positive direct effect in OCB, (2) Affective commitment has a positive direct effect in OCB, (3) perceived organizational support has a positive direct effect in affective comitment.